Comparison of clinico-epidemiological and radiological features in paracoccidioidomycosis patients regarding serological classification using antigens from Paracoccidioides brasiliensis complex and Paracoccidioides lutzii. - Edy F Pereira; Gregory Gegembauer; Marilene R Chang; Zoilo P de Camargo; Thiago F Nunes; Sergio M Ribeiro; Lídia R de Carvalho; Bianca M Maldonado; Rinaldo P Mendes; Anamaria M M Paniago (Public Library of Science (PLoS), 2020)
Genotyping of the genus Paracoccidioides showed its diversity and geographical distribution. Four species constituting the Paracoccidioides brasiliensis complex and Paracoccidioides lutzii are etiological agents of paracoccidioidomycosis (PCM). However, there are no studies comparing the clinical and epidemiological aspects between PCM caused by the P. brasiliensis complex and by P. lutzii. Demographic and clinical data from 81 patients with PCM-confirmed by mycological and/or histopathological examination-from Mato Grosso do Sul state (Brazil) were studied. All patients underwent serology by immunodiffusion with antigens obtained from the P. brasiliensis complex (ExoPb and gp43) and Cell Free Antigens obtained from P.lutzii (CFAPl).The cases were classified regarding their serological profile into three groups: G1: PCM patients seropositive to ExoPb and/or gp43 and seronegative to CFAPl (n = 51), assumed to have PCM caused by P. brasiliensis complex; G2: PCM patients seronegative to gp43 and seropositive to CFAPl (n = 16), with PCM caused by P. lutzii; and G3: PCM patients seropositive to ExoPb or gp43 and seropositive to CFAPl (n = 14), with undetermined serological profile, was excluded from the analyses. The Fisher's exact test or the Mann-Whitney U test, and cluster analysis according to Ward's method and Euclidean distance were used to analyze the results. Patients with serological profile suggestive of P. lutzii lived predominantly in municipalities in the Central and Southern regions of the state, while those with serological profile indicative of the P. brasiliensis complex were distributed throughout the state. No differences were found between the two groups regarding gender, age, schooling, rural work, clinical form, severity, organs involved, intensity of pulmonary involvement, degree of anemia, erythrocyte sedimentation rate values, and therapeutic response. PCM patients with serological profile suggestive of P. lutzii and PCM patients with serological profile indicative of P. brasiliensis complex showed the same clinical and radiological presentations.